FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN UNDERWEIGHT PADA ANAK USIA 24-59 BULAN DI NANGGROE ACEH DARUSSALAM (NAD): Analisis Data Surkesda NAD 2006 - Sri Mulyati; Sandjaja Sandjaja; Dwi Hapsari Tjandrarini (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2008)
Determinant Factors of The Incidence of Underweight Children Ageg 24-59 Month In Nanggroe Aceh Darussalam (NAD).Background: Surkesda NAD 2006 as post tsunami household health survey and covering all 21 districts/cities had assessed child nutritional status (underweight) for age 24-59 months, with cut-off point <-2.00 SD. A total sample of 1,437 children aged 0-59 months was included in the assessment.Objectives: The objective of this study is to analyze child nutritional status and factors related to the status in NAD after tsunami. The study revealed that the prevalence of underweight in NAD was 37.1% with ranges by districts from 15.8%-60.0%. The prevalence of underweight in NAD was higher than those of Indonesia.Methods: Multivariate analysis identified various factors that associated with the prevalence of underweight.Results: Children aged 24-59 months with higher risk of underweight were those suffering from infectious diseases other than upper respiratory tract infection or diarrhea (OR=1. 7) Cl; 1.028_2.792, those whose head of household had education less than senior high school (OR=1.45), Cl;1.088_1.946.Conclusions: Strategies to improve nutritional status of children should include accelerate nutrition intervention programs, improving accessibility for better basic health services, and other program related to health and nutrition which has to be part of community development.Keywords: children, underweight